(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2023)
The article presents the results of the analysis of Reportable Scheme Disclosure and the Fundamental Right to Non-Self-Incrimination, with the aim of protecting this right nationally and internationally. It employs qualitative research, analytical method, documentary technique, data collection instruments, the Mexican Constitution, international treaties such as the American Convention on Human Rights and the International Covenant on Civil and Political Rights, and the Federal Fiscal Code. The hypothesis: ’The use of reportable scheme disclosure as full proof of a tax offense violates the fundamental right to non-self-incrimination of the taxpayer and the tax advisor’ is confirmed.